VD_FINDINFO HC / 2011 / 404 vom 7. Juli 2011 - VD Tribunal cantonal (2011)
LITISPENDANCE, ADMISSION DE LA DEMANDE, DROIT DE LA FAMILLE, PRÉVOYANCE PROFESSIONNELLE | 124a CPC, 452 al. 2 CPC, 9 LDIP, 405 al. 1 CPC (CH)